Application of C4.5 Algorithm for Cattle Disease Classification. (July 2019) - Indra, Evta; Ho, Kevin; Arlinanda,; Hakim, Ridho; Sitanggang, Delima; Sihombing, Oloan
Abstract: Data mining is a series of process to gain values such as informations that is manually unknown from a database by mining patterns from the data (with the intention to manipulate data into more useful information that is obtained by extracting data and recognizing important pattern or pulling data from the database). The intend of this research is to process cattle disease cases, which so far no research has been done to produce useful knowledge/science for institutions (Food and Livestock Security Agency) using data mining technique (C4.5 Algorithm). In the future, this research will be used by Food and Livestock Security Agency to counsel rancher in some area. This research will result a decision tree which will also classify rate of cattle disease. Proven by using the C4.5 algorithm, it can speed up the process of classification disease which initially takes about 1-2 months, and after using this application the results can be obtained right away.